Audiobook collection selection at the Braille Library of Sentra Wyata Guna - Saepudin, Encang; Putri, Anneke; Khadijah, Ute Lies Siti (Faculty of Communication, Padjadjaran University, 2025)
Background: The information gap between the general public and persons with disabilities is a critical issue that must be addressed to foster a more inclusive society. Audiobooks serve as a vital solution in overcoming barriers to information access for individuals with visual impairments. Purpose: This study aims to examine the audiobook collection selection process at the Braille Library of Sentra Wyata Guna. Methods: A qualitative case study approach was employed, with data collected through documentation, interviews, observations, and literature review. Primary data were obtained from key informants selected purposively based on three main criteria. The four main informants included the chief audiobook editor, audiobook editorial staff, librarian, and a collection development expert. Data were analyzed interactively and continuously until completion, following the stages of data reduction, data presentation, and conclusion drawing. Results: The findings indicate that the Braille Library of Sentra Wyata Guna has taken significant steps in developing its audiobook collection. The selection process is conducted by an editorial board that determines which books are to be produced as audiobooks based on user needs and institutional requests. The selection process follows established standard operating procedures. In conclusion, the Braille Library of Sentra Wyata Guna has effectively implemented structured and accountable procedures in the selection of its audiobook collections.